The Role of Multinational Corporations in the Supply of Agricultural Production Technology to China & India. Issue 2 (1st March 2018) - Pray, Carl; Nagarajan, Latha; Naseem, Anwar
Abstract : Policy makers in Asia have long struggled with the challenge of how to access agricultural technology from multinational corporations (MNCs)while protecting their farmers and food and input industries from excess market power. This paper describes the pathways by which farmers can access technology and research capacity from foreign firms. Then it examines some of the policies that India and Chinese governments have used to encourage access. The recent history of research and technology transfer to these countries is reviewed to do a preliminary assessment of how these policies work. India has had a much more liberal policy on foreign investment in recent years which resulted in more access to MNC research and technology. So far, however, there are no studies that show this policy led to higher benefits to farmers or lower costs of transferring technology. Studies of benefits and costs of these policies could be very useful to Indian and Chinese policy makers.